Relationship Between Stress Level and Intensity of Social Media Use as Coping Media - Ghina Khairunnisa; Yaslinda Yaunin; Citra Manela (Lembaga Pengembangan Kinerja Dosen, 2024)
. Stress is defined as a non-specific reaction of the body when it comes to pressure that can interfere with bodily functions. The impact is that thesis work is delayed, and students complain on social media about the difficulties they are experiencing. All problems or demands faced by students require good preparedness and adjustment, so students need to have good preparation including coping with stress. This study was conducted to examine the relationship between stress levels and the intensity of using social media as a coping medium for 2018 students who are undergoing thesis at the Andalas University Medical Education Study Program. This study is a descriptive analytic study using 79 students who met the inclusion criteria and exclusion criteria. Data analysis using statistical tests, namely the Pearson Chi Square test. The test results obtained, there is a significant relationship between stress levels and the intensity of social media use with a p-value of 0.020 < 0.05 (p > 0.05). The results obtained are that there is a significant relationship between stress levels and the intensity of using social media as a coping medium in 2018 students who are undergoing Thesis at the Andalas University Medical Study Program.